Pengaruh Jarak Tanam terhadap Pertumbuhan Tanaman Jabon Putih (Anthocephalus cadamba Miq.) di Kabupaten Temanggung, Provinsi Jawa Tengah - Ardityana, Krisna; Kusumaningsih, Karti Rahayu; Hadi, Didik Surya (Fakultas Kehutanan Institut Pertanian STIPER Yogyakarta, 2024)
Anthocephalus cadamba Miq., is a type of tree from South and Southeast Asia which is currently widely cultivated by the community. Jabon has various uses such as block board and particle board. Apart from that, this plant is also known as a fast growing plant. Jabon farmers have their own way of caring for their plants, on of which is plant spacing. The goal of this research was to ascertain the impact of planting distance on survival rate and growth (height and diameter) of 1 year old Jabon plants in Temanggung Regency, Central Java. Data collection was carried out by taking 50 samples in each field consisting of 2x2 m, 3x3 m, and 4x4 m spread across 3 villages in Temanggung Regency. The replicates used were individual Jabon plants. Data from the research results were analysed using by analysis of variance, and tested further using the LSD test. The research results showed that land with a planting space of 3x3 m had a higher percentage of jabon plants than the land with a planting space of 2x2 m and 4x4 m, namely 71%. Land with a planting space of 2x2 m produce a better average height and diameter of jabon plants than of 3x3 m and 4x4 m, namely 1,39 m for height and 1,97 cm for diameter respectively.